Perilaku Konsumtif Muslim di Era E-Commerce: Tinjauan Etika Konsumsi dalam Perspektif Islam - Sazalia Naura Azzahra; Imsar Imsar (Journal Economic Excellence Ibnu Sina, 2025)
This study examines the phenomenon of Muslim consumer consumptive behavior in the digital era, focusing on online shopping activities through e-commerce platforms. The main goal is to examine the conformity of consumption behavior with the principles of consumption ethics in Islam. Using a qualitative descriptive approach, data was collected through in-depth interviews with selected Muslim consumers as well as observations of purchasing patterns over three months. The results show that the ease of access to technology, the intensity of promotion, and the influence of social media are the dominant factors that encourage impulse buying behavior. This phenomenon creates a gap between actual consumption practices and Islamic ethical values, especially related to the principles of moderation (wasathiyah), avoidance of waste (israf), and social responsibility in shopping. While some respondents showed awareness of these values, the pressures of the digital environment and consumptive lifestyles often obscure ethical considerations in purchasing decision-making. The implications of these findings emphasize the urgency of strengthening Islamic consumption literacy through digital education, awareness campaigns, and the integration of religious values in ethical marketing strategies. This research is expected to be the basis for the development of sustainable consumption policies based on spiritual values, as well as encourage Muslim consumers to be more critical and wise in facing the evolving dynamics of digital commerce.